Vertically transferred maternal immune cells promote neonatal immunity against early life infections - Ina Annelies Stelzer (Nature Portfolio, 2021)
Maternal immune cells seed into the foetus during mammalian pregnancy, yet the functional role of these cells is unclear. Here the authors show that maternal immune cells in foetal bone marrow stimulate immune development, subsequently reducing the risk or severity of infections in newborns.